Role of G Protein-Coupled Receptors in Microglial Activation: Implication in Parkinson’s Disease - Gu, Chao; Chen, Yajing; Chen, Yan; Liu, Chun-Feng; Zhu, Zengyan; Wang, Mei (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease (PD) is one of prevalent neurodegenerative diseases associated with preferential loss of dopaminergic (DA) neurons in the substantia nigra compacta (SNc) and accumulation of α-synuclein in DA neurons. Even though the precise pathogenesis of PD is not clear, a large number of studies have shown that microglia-mediated neuroinflammation plays a vital role in the process of PD development. GPCRs are widely expressed in microglia and several of them act as regulators of microglial activation upon corresponding ligands stimulations. Some of microglial GPCRs regulate α-synuclein degradation and clearance via phagocytosis or autophagy. Moreover, upon insults of α-synuclein, microglia would become excessive activated. The mechanistic relevance between microglial GPCR-mediated neuroinflammation and its role in PD pathogenesis remains unclear. Presently, as lack of ideal drugs for treating PD, a certain GPCR which is highly expressed in microglia of PD brain and mediates neuroinflammation effectively could be a prospective source for PD therapeutic intervention. Here, we highlighted the relationship between various GPCRs and microglial activation and their potential to become new expectation for clinical therapeutics in PD.